Hubungan Tingkat Kecemasan Dengan Timbulnya Acne vulgaris Pada Mahasiswa - Puspaciwi, Sanisca; Indah Widyaningsih; Rini Purbowati (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2024)
Background: One of the most common skin diseases found in young people is acne. The problem of acne will adversely affect the mentality of the sufferer. This study aims to analyse and determine the relationship between anxiety levels and the onset of Acne vulgaris in medical education students at Wijaya Kusuma University Surabaya class of 2020-2021. Methods: This study used a cross-sectional analytical observational research design, the population in this study were all students of the Faculty of Medicine, Wijaya Kusuma University Surabaya class of 2020-2021, totalling 156 students. The sampling technique is purposive sampling, with the calculation of the slovin formula, so that the number of samples is 70 respondents. The study used primary data and the analysis used was the chi square test. Result: The results showed that the level of anxiety in medical education students at Wijaya Kusuma University Surabaya Class of 2020-2021 was mostly in the high category. The description of the occurrence of Acne vulgaris in scientific students of Wijaya Kusuma University Surabaya class of 2020-2021 is mostly in the frequent category. There is a relationship between anxiety levels and the onset of Acne vulgaris in medical education students at Wijaya Kusuma University Surabaya class of 2020-2021